STRATEGI PENINGKATAN BRAND AWARENESS UNTUK MENDUKUNG PERSONAL SALES PADA PT. ALPHA CENTRAL PROPERTINDO - Fahlevi, Renza; Filrando, Ariendy (Bussman Journal : Indonesian Journal of Business and Management, 2025)
The increasingly competitive property industry requires companies to implement marketing strategies that enhance trust and strengthen brand recognition. One of the challenges faced by PT. Alpha Central Propertindo is the absence of an official promotional medium to consistently and professionally support personal selling activities. This study aims to design and implement a company profile as a strategy to enhance brand awareness and support personal sales at PT. Alpha Central Propertindo. This research adopts a descriptive qualitative approach using a community service model. Data were collected through observation, interviews, and documentation, while media development followed the Multimedia Development Life Cycle (MDLC) method. The results indicate that the implementation of the company profile had a positive impact on increasing consumer understanding and initial interest. Based on evaluations involving ten sales representatives, 80% reported improved consumer understanding of the company’s profile and services, while 70% indicated increased consumer interest after the use of the company profile. These findings suggest that a company profile serves as an effective promotional medium to support personal selling and enhance corporate brand awareness. This study provides practical implications for property service companies in optimizing visual promotional media as part of their marketing strategy